2020
DOI: 10.3390/metabo10110427
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Metabolic Differences between Hematopoietic Stem Cells and Acute/Chronic Myeloid Leukemia

Abstract: Although many studies have been conducted on leukemia, only a few have analyzed the metabolomic profiles of various leukemic cells. In this study, the metabolomes of THP-1, U937, KG-1 (acute myelogenous leukemia, AML), K562 (chronic myelogenous leukemia, CML), and cord blood-derived CD34-positive hematopoietic stem cells (HSC) were analyzed using gas chromatography-mass spectrometry, and specific metabolic alterations were found using multivariate statistical analysis. Compared to HSCs, leukemia cell metabolom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Therefore, additional in vivo experiments are required to verify the regulatory mechanisms in the present study. Second, K562 and HEL cells, which are acute myeloid leukemia-like cell line and human erythroleukemia cell line, and hematopoietic stem cells have certain similarities regarding erythropoietic development, but there are still some differences between the two cell types ( Deezagi, 2014 ; Song et al, 2020 ). Finally, the function of the EPAS1-IRS2 axis in K562 cell erythroid development has been researched here, but its precise molecular mechanism has not been completely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, additional in vivo experiments are required to verify the regulatory mechanisms in the present study. Second, K562 and HEL cells, which are acute myeloid leukemia-like cell line and human erythroleukemia cell line, and hematopoietic stem cells have certain similarities regarding erythropoietic development, but there are still some differences between the two cell types ( Deezagi, 2014 ; Song et al, 2020 ). Finally, the function of the EPAS1-IRS2 axis in K562 cell erythroid development has been researched here, but its precise molecular mechanism has not been completely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…However, an increasing body of evidence suggests that both glycolysis and mitochondrial metabolism are upregulated in some cancers [ 14 ]. It was found that both glycolysis- and OXPHOS-related signaling pathways are activated in leukemia cells, such as THP-1, U937, KG-1, and K562, as well as cluster of differentiation 34 (CD34)-positive hematopoietic stem cells (HSCs), as a result of an enhanced need for energy metabolism [ 15 ]. It has become clear that TKI-resistant AML and CML, and leukemic stem cells (LSCs) are accompanied by increased OXPHOS, regardless of the presence or absence of genetic mutations; hence, interest has grown in developing clinically applicable OXPHOS inhibitors [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each cell contains different types of metabolites because of the presence of individualized metabolic mechanism based on the fate of the cell. Thus, metabolic profiling has attracted considerable attention as an approach that can immediately detect dynamic cell changes and conditions, as well as early development [ 10 ]. Oncogenic mutations recurrently found in AML drive metabolic dysregulation, and dysregulated metabolism is closely linked to oncogenic addiction and thus potential therapeutic targets for AML.…”
Section: Introductionmentioning
confidence: 99%
“…Oncogenic mutations recurrently found in AML drive metabolic dysregulation, and dysregulated metabolism is closely linked to oncogenic addiction and thus potential therapeutic targets for AML. For example, mutation in the most common oncogene in AML, i.e., FLT3 , is known to be associated with glycolysis [ 10 ]. Other oncogenic driver mutations, such as those in MYC and RAS , have been studied to drive metabolic reprogramming, including increased glycolysis, glutaminolysis, lipid synthesis, and mitochondrial biogenesis, which are important for AML cell proliferation and survival [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation